Prevalence, antibiotic susceptibility and plasmid profile of bacteria from door knobs of female restrooms in BRAC University, Dhaka - Sultana, Innas (BRAC University, 2017)
This thesis report is submitted in partial fulfillment of the requirement for the degree of B.Sc in Microbiology, 2017.